Improvement of office chair for ergonomics purpose - Mohamad Izzat, Mohamad Yuden (2008)
Ergonomic is the application of scientific principles, methods and data to the development of products and systems that interact with human. A product may be ergonomically designed for a specific application. The product selected must be matched the characteristics of the required operations and the characteristics of the people who use the products. Correct sitting posture is an important factor for the prevention of musculoskeletal symptoms. Then, ergonomic furniture should be designed because it can reduce pain and injury, increase productivity, improve morale and decrease complaints. Office chair has been one of the most required furniture for over hundreds of years especially for office use. However, as the increasing of the demand to produce the office chair, there are several problems commonly occur to clerk. So, the main objectives of this project are to improve the design of office chair with ergonomic features for the office use and to minimize the risk factor of musculoskeletal disorders faced by the clerk. At the end of this project, a new design of office is proposed by using Solid Work software. There are some improvements have been made to the some parts of existence office chair including back support, seat pan, armrest and seat height. The proposed design is different in terms of shape, measurement and also equipped with the ergonomic features. As the result of this improvement, the objective to reduce disorders faced by the clerk can be achieved.